The Enigma of Humanistic Justice in Addressing Narcotics Abuse - Maria Febriana; Mohammad Haris Yusuf Albar; Adiyansyah Lukman Hakim (Mimbar Keadilan, 2024)
Drug abuse is a complex problem that requires a comprehensive solution. This includes how the concept is used in various aspects of tackling drug abuse. Justice in drug abuse eradication is a complex enigma, especially when the approach taken tends to be repressive and pays less attention to humanitarian aspects. Restorative justice is an alternative paradigm for handling drug abuse in Indonesia by linking it to the values of Pancasila. Restorative justice emphasizes recovery, reconciliation, and reintegration of offenders, victims, and society. This approach is in line with Pancasila values such as humanity, unity, and social justice. Restorative justice does not only enforce the law, but also pays attention to the social and psychological aspects involved in drug abuse cases. Applying restorative justice to the rehabilitation of drug addicts helps them overcome their addiction and become productive members of society again. Implementing restorative justice requires the cooperation of various stakeholders, including government, law enforcement, and local communities. This research aims to explore and understand the complexity of humanistic justice in the context of drug abuse treatment, as well as examine the definition and concept of humanistic justice in the context of drug abuse. This research uses an empirical juridical method, with interviews conducted at the Kediri City Attorney's Office and observation visits to post-rehabilitation drug abusers. Results of this study show that to overcome this, a comprehensive approach is needed that affects many aspects of life. The noble values of Pancasila provide a solid foundation in developing effective coping strategies.